Structural Behavior of Normal and High Strength Concrete Wall Panels Subjected to Axial Eccentric Uniformly Distributed Loading - M. AL-Khafaji, Jasim (Anbar Journal of Engineering Sciences, 2012)
In most cases, the concrete wall panels are subjected to axial eccentric distributed loading; due to this type of loading, concrete wall panels behave and fail somehow. There are many parameters that affect the structural behavior of the concrete wall panels. This study presents experimental investigation the structural behavior of concrete wall panels subjected to axial eccentric distributed loading; also evaluates the effect of the parameters, slenderness ratio (H/t), aspect ratio (H/L) and concrete strength on the behavior of concrete wall panels. The experimental program includes testing fifteen concrete wall panels hinged at top and bottom with free sides, by applying the load axially with eccentricity equal to (t/6); these panels are divided into five groups, each group consists of three panels with slenderness ratio (H/t) equals to (20 , 25 , 30) for each panel, three groups of normal concrete strength with aspect ratio (H/L) equal to (1.0 , 1.5 . 2.0) for each group and the other two groups are of high strength concrete with aspect ratio (H/L) equal to 2.0 for both two groups. The deflections of concrete wall panels depend on the slenderness ratio (H/t), aspect ratio (H/L) and concrete strength. The failure mode of the concrete wall panels is greatly affected by the aspect ratio (H/L); the panels with low aspect ratio tend to fail by crushing, while panels with high aspect ratio tends to fail by buckling.